Food premises inspection violations and inspection frequency during COVID-19 in Vancouver Island Health Authority - Smith, Jessi; BCIT School of Health Sciences, Environmental Health; Heacock, Helen (BCIT Environmental Public Health Journal, 2022)
Food service establishments, such as restaurants are subject to regulatory compliance, which acts to protect the health of the public from health risks and hazards that may arise in these settings. Ensuring compliance during inspections is carried out by public health professionals including Environmental Health Officers (EHOs). The COVID-19 Pandemic has impacted the public health sector, with many programs, services and professional involvement being enhanced to better support the COVID-19 response. This study investigated whether restaurant inspections on Vancouver Island, British Columbia, were impacted during COVID-19, including inspection frequency, inspection violations and hazard ratings.